2020
DOI: 10.3390/biom10091228
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Astrocyte and Microglia Endocannabinoid Signaling during Autoimmune Demyelination

Abstract: The endocannabinoid system is associated with protective effects in multiple sclerosis (MS) that involve attenuated innate immune cell responses. Astrocytes and microglia are modulated by endocannabinoids and participate in the biosynthesis and metabolism of these compounds. However, the role of neuroglial cells as targets and mediators of endocannabinoid signaling in MS is poorly understood. Here we used a microfluidic RT-qPCR screen to assess changes in the expression of the main endocannabinoid signaling ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Thus, in parallel with the in vitro data showing that MSC attenuate the RNA expression of the A1 marker Serpin G1 that was induced by exposure of astrocytes to IFN‐γ, we immunolocalized complement factor C3, as marker of A1 phenotype in vivo, on brain sections from naïve and EAE‐affected mice treated or not with MSC. Our data confirmed a previous report (Moreno‐García et al, 2020) indicating that reactive astrocytes in EAE overexpress the A1 marker C3, and demonstrated that administration of MSC diminished the number of C3‐expressing A1 astrocytes to the levels detected in naïve mice (Figure 3a). Thus, in order to establish whether or not MSC, besides attenuating the A1 phenotype, may promote the acquisition of a neuroprotective trait in reactive astrocytes, we immunolocalized S100A10 as a marker of A2 astrocytes, in the same experimental groups.…”
Section: Resultssupporting
confidence: 93%
“…Thus, in parallel with the in vitro data showing that MSC attenuate the RNA expression of the A1 marker Serpin G1 that was induced by exposure of astrocytes to IFN‐γ, we immunolocalized complement factor C3, as marker of A1 phenotype in vivo, on brain sections from naïve and EAE‐affected mice treated or not with MSC. Our data confirmed a previous report (Moreno‐García et al, 2020) indicating that reactive astrocytes in EAE overexpress the A1 marker C3, and demonstrated that administration of MSC diminished the number of C3‐expressing A1 astrocytes to the levels detected in naïve mice (Figure 3a). Thus, in order to establish whether or not MSC, besides attenuating the A1 phenotype, may promote the acquisition of a neuroprotective trait in reactive astrocytes, we immunolocalized S100A10 as a marker of A2 astrocytes, in the same experimental groups.…”
Section: Resultssupporting
confidence: 93%
“…We now demonstrate that microglia CB2R mRNA level was 162 ± 63-fold higher than that of neurons in adult mouse brain. Since CB2R in microglia is also inducible [ 57 , 58 ], the purified microglia CB2R expression may not reflect that of naïve microglia. Our finding of increased expression of neuron CB2R by methamphetamine treatment agrees with previous findings of neuron CB2R upregulation by brain stressors such as cocaine [ 59 ], traumatic brain injury [ 60 ], seizure [ 61 ], and ischemia [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In EAE, increased endocannabinoid levels in the brain, cerebellum, and plasma of C57BL/6 mice treated with a selective endocannabinoid reuptake inhibitor, WOBE437, correlated with significant muscle relaxation, decreased neuroinflammatory infiltration, and lower microglial proliferation [187]. Dynamic transcriptional deregulation in the endocannabinoid system during EAE results in an early shift toward enhanced 2-AGmediated CB1 receptor activation in astrocytes that is followed by deficits at later stages of the disease [188].…”
Section: Elucidating the Molecular Mechanisms Of Medical Marijuana Th...mentioning
confidence: 99%